Cardiologic evaluation of children with suspected heart disease: experience of a public outpatient clinic in Brazil - Amaral, Fernando; Granzotti, João Antonio (São Paulo Medical Journal, 1999)
CONTEXT: During initial evaluation of children on an outpatient basis, the index of suspected heart disease may be high, particularly if we consider that innocent murmur occurs in about 50% of the pediatric population. This is the most common cause of referral to the pediatric cardiologist. OBJECTIVE: To report on the experience of a public outpatient clinic in the southeastern region of Brazil. DESIGN: Retrospective analysis of all patients submitted to cardiologic evaluation within a 39 month period. SETTING: public pediatric cardiology outpatient clinic. PARTICIPANTS: 2675 consecutive children aged £15 years referred from the local and regional basic health units due to suspected heart disease. MAIN MEASUREMENTS: Reason for referral, diagnostic investigation, final diagnostis based on the reason for referral, therapeutic procedures. RESULTS: The main reasons for referral were: murmur (70%), precordial pain (9%), suspicion of arrhythmia (9%) and breathlessness (5%). Of the total number, 695 cases (26%) did not complete the investigation and were not included in the analysis. A final diagnosis was obtained based on the reason for referral and the main conclusions were: l) a high incidence of normality was found: murmur (83%), pain (98%), arrhythmia (97%) and breathless (94%); 2) heart disease was unlikely, based on other referral reasons; 3) 14% of the children were considered abnormal and 1% needed therapeutical procedures. CONCLUSIONS: The establishment of a pediatric cardiology outpatient clinic within the public health service in the region seems to be justifiable, due to the high current demand. The low global incidence of heart disease, with a high prevalence of children with innocent murmur, discloses the need for a specific training program in cardiology for pediatricians.